HLA-DR Mismatch and Black Race Are Associated With Recurrent Autoimmune Hepatitis After Liver Transplantation. Issue 7 (10th June 2021) - McCabe, Marshall; Rush, Natalia; Lammert, Craig; Patidar, Kavish R.; Nephew, Lauren; Saxena, Romil; Ekser, Burcin; Salven, James; Kubal, Chandrashekhar; Ghabril, Marwan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The predictors of recurrent autoimmune hepatitis (R-AIH) after liver transplantation (LT) are heterogeneous with limited data to guide immunosuppression, with little data on impact of race. Aims: To describe the incidence, predictors, and outcomes of R-AIH. Methods: We studied patients undergoing LT for AIH during 2000–2017 at our center. Liver biopsies were performed for clinical indications. R-AIH was defined using clinical and histologic criteria. Results: Among 75 patients undergoing LT for AIH (mean age 45 ± 16, 65% female individuals, 19% Black), 71 (95%) received antithymocyte globulin induction with tacrolimus-based immunosuppression. R-AIH developed in 20 (27%) patients at a median interval of 313 d (interquartile range, 155–1205). R-AIH was associated with level 2 HLA-DR mismatch (hazard ratio, 3.6; (95% confidence interval, 1.3-9.9; P = 0.01) and Black race (hazard ratio, 4.5; 95% confidence interval, 1.8-11.8; P = 0.002)] in the multivariable analysis. R-AIH developed in 62% of patients with level 2 HLA-DR mismatch on single-agent immunosuppression but in <20% of patients with no or 1 HLA-DR mismatch regardless of maintenance immunosuppression. R-AIH developed in 8 (57%) of 14 Black patients (71% on single-agent and 43% on dual-agent maintenance immunosuppression). Patient and graft survival were not impacted by R-AIH over a median follow-up of 8.3 y (interquartile range, 3–12). Conclusions: High-level HLA-DR mismatch and Black recipient race are associated with an increased risk of R-AIH. Immunosuppression did not predict R-AIH, but higher rates of disease recurrence with single-agent maintenance immunosuppression with these risk factors were observed and may guide maintenance immunosuppression in LT for AIH.